Cafés d’Haïti et cafés de l’ailleurs: Ollivier, Jean-Claude Charles, Dany Laferrière - Pessini, Alba (Ponti/Ponts, 2021)
characters of Haitian fiction are usually found in the typical Haitian aggregation sites, the galerie, “la glacière” de La Discorde aux cent voix d’Émile Ollivier, the barber shop Zag des Urnes scellées, but also outside the walls of the houses, in public places such as cafés. These are often open spaces since the residents of Haiti like living, as often happens in many tropical societies, outside of the narrow space of the houses. Such places are found in the works of many writers, from Jacques Stephen Alexis (le Sensation Bar from the novel L’espace d’un cillement) to Émile Ollivier (La Brûlerie, café de Montréal, that Dany Laferrière, in the Introduction to this posthumously published novel defined as “la banlieue de Port-au-Prince”) not to mention Jean-Claude Charles whose very title of one of his novels is the name of a bar, Bamboola Bamboche, and Dany Laferrière where the narrator transforms the public space of the café into an observation point on what is happening around him. The highlight of the last book of the first Canadian-Haitian writer to come under the Coupole des Immortels, L’Art presque perdu de ne rien faire, is a quote of Aragon: “La vie c’est changer de café”. We propose, then, in this paper, with the work of three writers of the Haitian diaspora (Émile Ollivier, Jean-Claude Charles et Dany Laferrière) to investigate the place and role that space plays in various fictions, be they located in Haiti or in the migrants’ host country and especially if that status changes once the characters experience exile.